APLIKASI MAKNA MITOS BANYU DALAM BAHASA BANJAR [The Application of Mythical Meaning of “Banyu” in Banjar Language] - Rissari Yayuk (TOTOBUANG, 2018)
This research studied about how the mythical meaning of Banyu (water) applyed in Banjar language based on the lexicon  and contextual source. The purpose of this research was describing the myth meaning of Banyu in Banjar language based on its lexicon source and the function based on its contextl. The research method was qualitative descriptive.The data collection techniques had used  observing-conversation  technique. The frame of work was data collection, data processing, and results of data analysis. The sampling technique that used in this paper was the purposive sampling, the sampling technique of data source collection with considering. The data collection that had been takenfrom January  to December 2017. The place where data were collectedwas at Padang Village, Banjar Regency. The data presentation was using ordinary words. The result showed thath  myth meaning of Banyu that applyed in Banjar language based on lexicon source consisted of  original source, material, and pars proto whilee based on contextual were ordinary and magical, or religious. Later, it was used  as regular drinking water,  therapy water, and  medication.Penelitian ini mengkaji tentang bagaimana aplikasi makna mitos Banyu pada bahasa banjar berdasarkan sumber leksikon dan  kontekstual. Tujuan penelitian meliputi deskripsi aplikasi makna mitos banyu pada bahasa banjar berdasarkan sumber leksikon dan fungsi Banyu dalam bahasa Banjar berdasarkan kontekstual.  Metode yang digunakan adalah deskrieptif kualitatif. Teknik pengambilan data adalah simak dan libat cakap. Langkah kerja adalah pengumpulan data, pengolahan data, dan hasil analisis data. Teknik pengambilan sampel yang digunakan dalam tulisan ini adalah  purposive sampling, yaitu teknik pengambilan sampel sumber data yang mempertimbangan waktu pengambilan data pada bulan Januari sampai  bulan desember 2017. Tempat pengambilan data di Desa Padang, Kabupaten Banjar. Penyajian data  menggunakan kata-kata biasa. Hasil penelitian aplikasi makna mitos banyu pada bahasa banjar berdasarkan sumber leksikonnya terdiri atas sumber asal, bahan, dan pars proto, sedangkan berdasarkan konstektual  bersifat biasa dan magis, atau religi. Ada yang difungsikan sebagai air minum biasa, terapi, dan  pengobatan.